A winter wedding - Forester, Amanda (Sourcebooks Casablanca, 2014)
The Duke of Marchford requires a suitable bride, but catching spies for the Foreign Office takes up most of his time. Not wanting to face another London season as an eligible man, he employs the notorious Madame X to find him a match. Miss Penelope Rose knows the rules of marriage among members of the ton better than most. Her own unsuccessful attempts at matrimony did not stop her from becoming London's most exclusive matchmaker. Marchford proves to be a difficult client, but as he draws on her social expertise to help him flush out a dangerous traitor, they find that falling in love may be the riskiest adventure of all.